2010
DOI: 10.1074/jbc.m109.071035
|View full text |Cite
|
Sign up to set email alerts
|

Sequestering of Rac by the Yersinia Effector YopO Blocks Fcγ Receptor-mediated Phagocytosis

Abstract: Pathogenic Yersinia species neutralize innate immune mechanisms by injecting type three secretion effectors into immune cells, altering cell signaling. Our study elucidates how one of these effectors, YopO, blocks phagocytosis. We demonstrate using different phagocytic models that YopO specifically blocks Rac-dependent Fc␥ receptor internalization pathway but not complement receptor 3-dependent uptake, which is controlled by Rho activity. We show that YopO prevents Rac activation but does not affect Rac accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…Upon translocation into the host cell, the N terminus of YpkA localizes the protein to the inner surface of the host cell plasma membrane, where it is in close proximity to key proteins involved in transducing extracellular signals into eukaryotic cells. Groves et al demonstrated the importance of YpkA subcellular localization to the plasma membrane for RhoGTPase binding (33). YpkA was shown to selectively inhibit Rac-dependent Fc␥ receptor-mediated phagocytosis by specifically targeting endogenous membranebound Rac isoforms in cells (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon translocation into the host cell, the N terminus of YpkA localizes the protein to the inner surface of the host cell plasma membrane, where it is in close proximity to key proteins involved in transducing extracellular signals into eukaryotic cells. Groves et al demonstrated the importance of YpkA subcellular localization to the plasma membrane for RhoGTPase binding (33). YpkA was shown to selectively inhibit Rac-dependent Fc␥ receptor-mediated phagocytosis by specifically targeting endogenous membranebound Rac isoforms in cells (33).…”
Section: Discussionmentioning
confidence: 99%
“…A region within the C-terminal domain (residues 431-612, RhoGDI) of YpkA possesses Rho GTPase binding guanine nucleotide dissociation inhibitor (GDI)-like activity and has been shown to be important for inactivation of the small Rho GTPases, RhoA and Rac1 (32). The GDI-like activity interferes with phagocytosis by disrupting the host actin cytoskeleton (33). Substitution of three amino acids (Y591A, N595A, E599A) in the GDI-like domain interferes with Rho GTPase binding (32).…”
mentioning
confidence: 99%
“…In 2004, Carolyn et al found that alphastatin could inhibit angiogenesis in vitro, and could inhibit tumour angiogenesis in mice (Groves et al, 2010). Experiments revealed that alphastatin could inhibit angiogenesis by vascular endothelial cells in vitro as well as murine CT26 tumour angiogenesis without side effects, showing good potential (Raffaniello et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Typhimurium translocates effector proteins (SipA, SipC, SopE, SopE2, and SopB/SigD) into nonphagocytic cells via T3SS1 to induce a "triggering" mode of uptake, whereas Y. enterocolitica translocates effectors (YopE, YopH, YopO, and YopT) into phagocytic cells to inhibit its own uptake (17,19,25,29). When Y. enterocolitica is added to host cells first, S. Typhimurium invasion drops to a level similar to that of an S. Typhimurium invA mutant, which lacks T3SS1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1B is also a food-borne pathogen and, like S. Typhimurium, translocates numerous T3SS effector proteins, called Yops, into the host cell cytosol using both the Ysc T3SS encoded on the virulence plasmid, pYV, and the Ysa T3SS encoded on the chromosome (25)(26)(27)(28)(29). However, in contrast to S.…”
mentioning
confidence: 99%